2014
DOI: 10.1186/1479-5876-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Donor age negatively impacts adipose tissue-derived mesenchymal stem cell expansion and differentiation

Abstract: BackgroundHuman adipose tissue is an ideal autologous source of mesenchymal stem cells (MSCs) for various regenerative medicine and tissue engineering strategies. Aged patients are one of the primary target populations for many promising applications. It has long been known that advanced age is negatively correlated with an organism’s reparative and regenerative potential, but little and conflicting information is available about the effects of age on the quality of human adipose tissue derived MSCs (hAT-MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
373
6
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(416 citation statements)
references
References 38 publications
31
373
6
6
Order By: Relevance
“…In fact, there have been mixed results in the differentiation characteristics of these cells. It is likely that the age of the donor from which the stem cells are derived will affect the differentiation properties [74]. Together with our findings, it appears that the TM stem/ progenitor cells are present in both primate and non-primate animals.…”
supporting
confidence: 69%
“…In fact, there have been mixed results in the differentiation characteristics of these cells. It is likely that the age of the donor from which the stem cells are derived will affect the differentiation properties [74]. Together with our findings, it appears that the TM stem/ progenitor cells are present in both primate and non-primate animals.…”
supporting
confidence: 69%
“…This is difficult because it is not easy to get ovarian tissue, especially in younger women. We can only speculate on an ideal age based on the literature; this age could be under 30 years-old [34]. Moreover, our data showed that the female age did not affect the characteristics of PO-MSCs and that even in the oldest patient, aged 75 years, PO-MSCs expressed a high potential to differentiate into adipogenic in osteogenic cells.…”
Section: Discussionmentioning
confidence: 88%
“…It could be expected that aging negatively affects the characteristics of MSCs and has an impact on gene expression, although we did not observe this. Some studies have shown that aging increased senescence and reduced cell viability, proliferation and differentiation potential [34][35][36]. Furthermore, when performing in vitro studies, the long-term expansion of MSCs had a significantly negative impact on the characteristics of MSCs, regardless of donor age [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, adipose tissue derived stem cells have been the most favourable cell source for research and clinical application because of their dominant characteristics (Bassi, 2012;Choudhery et al, 2014;Melief et al, 2013). Therefore, an important step forward for the treatment of diabetes would be to differentiate these cells into insulin-producing cells.…”
Section: Discussionmentioning
confidence: 99%